Case report: Antibodies to myelin basic protein in a podenco-crossbreed dog with seizures - Deutschland, M.; Boettcher, I.; Höltje, M.; Prüss, H. (Frontiers in Veterinary Science, 2024)
A 6-year-old female spayed Podenco-crossbreed dog was presented with an unusual type of focal impaired awareness seizures, including sensory ataxia and postictal rest. Magnetic resonance imaging examination revealed pre- and post-contrast agent T1-weighted bilateral symmetric hyperintensities in the lentiform nuclei and globus pallidus. Repeated cerebrospinal fluid sampling showed lymphocytic pleocytosis. Cerebrospinal fluid immunoglobulin G autoantibodies to myelin basic protein (MBP) were detected by immunofluorescence examination with strong binding to myelinated fiber tracts. The absence of binding to MBP-depleted mouse brains confirmed MBP as an antigenic target. Although the patient had minor seizure episodes every 2 months, and the owners avoided seizure triggers, they refused medical treatment before presenting to the veterinarian. To the best of our knowledge, this is the first description of MBP autoantibody-positive encephalitis in a dog.